1973
DOI: 10.1063/1.1654764
|View full text |Cite
|
Sign up to set email alerts
|

Role of coating defects in laser-induced damage to dielectric thin films

Abstract: The laser-induced damage thresholds of two different dielectric thin-film coatings increased with decreasing spot size and were invariant for spot sizes greater than 150 μm. A simple model has been suggested that the distribution and nature of coating defects have played an important role in this spot-size dependence, e.g., the probability of the laser beam striking a defect site will be greater for larger spot sizes and that damage in materials can be distinguished as defect damage and intrinsic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 1 publication
1
31
0
1
Order By: Relevance
“…Based on this experimental result, we cannot use the plasma mirror effect to explain the dependency shown in Figure 5. In addition to the plasma mirror effect, the above-mentioned dependence of damage threshold on spot size can be also attributed to a defect-dominated mechanism, as reported in previous experiments in nanosecond and femtosecond regimes [11,12]. In these studies, the probability of the laser beam impinging on a point-like defect site, which is assumed to be more strongly absorbing than the pure fused silica, is higher for a larger beam size.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Based on this experimental result, we cannot use the plasma mirror effect to explain the dependency shown in Figure 5. In addition to the plasma mirror effect, the above-mentioned dependence of damage threshold on spot size can be also attributed to a defect-dominated mechanism, as reported in previous experiments in nanosecond and femtosecond regimes [11,12]. In these studies, the probability of the laser beam impinging on a point-like defect site, which is assumed to be more strongly absorbing than the pure fused silica, is higher for a larger beam size.…”
Section: Discussionmentioning
confidence: 76%
“…where d 0 is the mean distance between two defects and is related to the mean defect density ρ 0 [11,12]. For very small spot size, one can thus expect the laser beam hitting no defect and that the threshold determined in this condition corresponds to the intrinsic surface damage threshold F th,int of the material, depending on its structural arrangement and nature of constituents.…”
Section: Discussionmentioning
confidence: 98%
“…Nagilhou et al (2015) [29] recently presented data that supports that notion for poly(styrene) in their extension of the defect model [30]. However, the fact that this phenomenon was only observed on some of the polymers and that it was accompanied with some sort of coloration could also indicate that photochemical reactions are taking place.…”
Section: Optical Characterizationmentioning
confidence: 78%
“…crystallography, microstructure, anisotropy, chemical composition, defects) and the ultraviolet (248 nm) or near infrared (1064 nm) laser damage thresholds are also reviewed [8]. In addition, a simple model suggested that the distribution and feature of coating defects played an important role in the laser-induced damage [9]. Up to now, there were some experimental and theoretical studies about effects of coating defects on laser-induced damage [10,11].…”
Section: Introductionmentioning
confidence: 98%